Use of nutricosmetic based on proteoglycan in non-cicatricial alopecia in children and adolescents - Kondo, Rogério Nabor; Gon, Airton Dos Santos; Ramos, Paulo Muller [UNESP] (GN1 Sistemas e Publicacoes, 2020)
Introduction: Nutricosmetics have been used as supplements for hair growth in the treatment of non-cicatricial alopecia. However, there are no studies on using of these products in individuals under 18 years of age. Objective: To assess the efficacy and tolerability of using a nutricosmetic product based on proteoglycans in individuals under 18 years of age with non-cicatricial alopecia. Methods: This is a clinical, uncontrolled, and prospective trial. Patients with non-cicatricial alopecia, of both sexes, aged between 6 years and 18 years, received nutricosmetics containing proteoglycan for six months. Three dermatologists independently evaluated standardized pre and post-treatment photos. A hair count was performed in a scalp area of 1 cm2, and the patients answered a questionnaire about improvement or worsening. Results: Eleven patients (100% women) were included. Ten (91%) showed improvement after six months, observed through photographic evaluation, hair count, and self-assessment. No patient presented allergies. Two patients had transient epigastric pain. Conclusions: The use of proteoglycans-based nutricosmetics was effective and well-tolerated in children and adolescents with non-cicatricial alopecia.
Uso de nutricosmético à base de proteoglicanos em alopecias não cicatriciais em crianças e adolescentes
Keywords: Alopecia; Hair follicle; Proteoglycans; Treatment outcome